Analysis of Competitiveness and Export Performance: Indonesian Crude Palm Oil (HS 15111000) Commodity against Major Competitor in Indian Market - Harpy, Meyva; Taufiq, M.; Utami, Anisa Fitria (Journal of Business Management and Economic Development, 2024)
International trade has become a key pillar in driving a country's economic growth. The stability of international trade is reflected in export-import activities. The amount of exports that exceeds the amount of imports will increase national income and positively affect the country's economic growth. Crude Palm Oil (CPO) is Indonesia's dominant export product that plays a critical role in the country's economic growth. Indonesia's CPO production in 2018 was recorded at 40.57 million tons. India is Indonesia's largest main market in exporting CPO. The purpose of this study is to determine the competitiveness and performance of Indonesia's CPO exports compared to the main competitor countries, namely Malaysia and Thailand. The data analysis process utilizes Revealed Comparative Advantage (RCA), Constant Market Share (CMS), and the Man-Whitney Test with the period of research statistics from 2013-2022.The results show that Indonesia's RCA value has competitiveness and comparative advantage in CPO exports against Thailand, but does not show significant differences with Malaysia in the Indian market. The results of data analysis using Constant Market Shares (CMS) to measure Indonesia's CPO export performance through standard growth, commodity composition effects, market distribution effects and competitiveness effects show that the export performance of CPO commodities against major competitor countries in the Indian market tends to have a positive trend.